Aulin V., Zamota T., Lysenko S., Hrynkiv A., Chernai A. Tribology transitions at running-in of friction surfaces conjugate parts. - Аулин, В. В.; Замота, Т. Н.; Лысенко, С. В.; Гринькив, А. В.; Чернай, А. Е. (Problems of Tribology, 2018)
Running-in is the process of difficult tribology transitions of surfaces of friction from the new state (after making or repair) to running-in one. Completion of running-in comes after stabilizing of basic tribotechnical descriptions of surfaces and parameters of process of friction. Testifies conformity to law of running-in that investigating flowing of processes is possible three basic methods: on measuring of moment of friction; at times passing of interface to the stable state; on descriptions of short-term changes of force of friction. Determination of basic conformities to law will allow to promote efficiency of running-in of friction surfaces of details of machines